Willingness to pay for community based health insurance scheme among pregnant women in Lagos State (2016)
The Nigerian population has a predominantly rural populace and over 90% of the population do not have access to the National Health Insurance scheme due to the highly informal nature of the economy. The use of the Community Based Health Insurance Scheme (CBHIS) is vital to health status especially among pregnant women given that the Nigerian economy is the second largest contributor to global under-five and maternal deaths. This paper examined the Willingness to pay (WTP) for the use of the CBHIS and premium amounts WTP in rural parts of Lagos State. The study made use of the probit model to examine factors that affect the WTP and measures of central tendency to determine the premium charge that pregnant women are WTP for use of the scheme. Data was obtained from a cross section of 350 pregnant women in three different CBHIS centers in Lagos State Results of the study suggest that income, employment status, household size, marital status and distance to the CBHIS significantly determine the WTP for the use of the CBHIS. Use of the CBHIS would be relatively high when monthly premium is set at N 500. The average amounts that pregnant women are WTP for use of the scheme was about N1,186.40 (US $6.02) per month. Efforts meant to raise the use of the CBHIS in rural communities by pregnant women, should incorporate strategies that will reduce premium payment below existing rate and create enlightenment of benefits of the scheme particularly for women in self-employment.